Recent meteorological and marine studies to support nuclear power plant safety in Finland. (15th December 2018) - Jylhä, Kirsti; Kämäräinen, Matti; Fortelius, Carl; Gregow, Hilppa; Helander, Juho; Hyvärinen, Otto; Johansson, Milla; Karppinen, Ari; Korpinen, Anniina; Kouznetsov, Rostislav; Kurzeneva, Ekaterina; Leijala, Ulpu; et al.
Abstract: Major nuclear accidents are typically low-probability–high-consequence events. This paper focuses on weather and sea-level events that might affect the safety of nuclear power plants (NPPs). Flooding risks at Finnish NPP sites have been re-evaluated based on investigations of long-term changes and short-term variations in sea level, which has led to improvements in the protection against extremely high sea water level. Climate change projections indicated that 1000-year return levels of high enthalpy of the air would increase by 13–27% by 2100. However, no clear future trends were projected for the all-year-round probabilities of freezing rain at the NPP sites. Simulations of the spread of hypothetical radioactive releases during two sea-breeze cases, using weather input data at a remarkably high spatial resolution, demonstrated the impacts of coastal meteorological phenomena on atmospheric dispersion. Overviews of various single and combined weather and marine events that could possibly affect normal NPP operation highlighted the need to broaden the scope of future research. Special attention was focused on various aspects of uncertainty. According to the results, a more extreme weather or marine event corresponded to a larger uncertainty in its probability of occurrence in the changing climate. Highlights: Safe production of nuclear energy requires appraisal of weather and sea-level risks. Changing climate affects the occurrence of extreme weather and sea-level events. Land uplift will moderate the increase of flooding risks on the Finnish coast. Progress in data and methods reveals new potential hazards such as meteotsunamis. High-resolution meteorological data is vital as input for dispersion modelling.